Organizational Sacralization: Scale Development and Validation - Sengullendi, Muhammet Fatih; Sehitoglu, Yasin (IGIAD-TURKISH ENTREPRENEURSHIP & BUSINESS ETHICS ASSOC, 2023)
This study aims to develop the Organizational Sacralization Scale, organizational sacralization involving how the concept of the sacred, the existence of which dates back to the earliest periods of humanity, is currently re-flected in organizations. This study first tests the content validity of the Organizational Sacralization Scale. The next stage is the pilot study phase, in which validity and reliability tests are conducted for the scale using data obtained from 116 white-collar employees. The next stage tests the construct validity of the scale within the scope of data obtained from 215 white-collar employees. The research results show the concept of organizational sacralization to be a scientifically measurable and psychometrically valid and reliable concept consisting of 13 items in three subdi-mensions: seeking meaning, providing meaning, and legitimating meaning
Keywords: Organizational sacralization; scale development; content validity; construct validity; reliability; sacred; organizational values; SUPPLEMENTARY FIT; LEGITIMACY; VALIDITY; VALUES; WORK; COMPLEMENTARY; DRAGONFLIES; BEHAVIOR; TESTS; MODEL; Business & Economics